2017
DOI: 10.1055/s-0043-120922
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Cancer and Coexisting Autoimmune Thyroiditis

Abstract: Histological findings often display an association between papillary thyroid carcinomas (PTC) and autoimmune thyroiditis (AIT) and so differ significantly from follicular thyroid carcinomas (FTC). The aim of this interdisciplinary, retrospective study was to evaluate the association of AIT in patients with PTC and FTC and a control group of benign nodular goiters. One hundred thyroidectomies with histologically confirmed differentiated thyroid carcinomas, 67 with PTC and 33 with FTC, were submitted for examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…Similar to the studies published until 2011 (see above), numerous retrospective studies using surgical specimens reported the high-er prevalence of lymphocyte infiltration and/or anti-thyroid autoantibodies (anti-Tg and/or anti-TPO) in patients with PTCs as compared to those with other types of thyroid cancers or benign goiters/nodules [10,11,[13][14][15][16][17][18][19][20][21] (▶table 1). The majority of Hashimoto's patients have anti-Tg and/or anti-TPO antibodies, and the minority of healthy subjects have these antibodies without intrathyroidal lymphocyte infiltration.…”
Section: Studies With Surgical Specimensmentioning
confidence: 56%
See 1 more Smart Citation
“…Similar to the studies published until 2011 (see above), numerous retrospective studies using surgical specimens reported the high-er prevalence of lymphocyte infiltration and/or anti-thyroid autoantibodies (anti-Tg and/or anti-TPO) in patients with PTCs as compared to those with other types of thyroid cancers or benign goiters/nodules [10,11,[13][14][15][16][17][18][19][20][21] (▶table 1). The majority of Hashimoto's patients have anti-Tg and/or anti-TPO antibodies, and the minority of healthy subjects have these antibodies without intrathyroidal lymphocyte infiltration.…”
Section: Studies With Surgical Specimensmentioning
confidence: 56%
“…Anti-Tg antibodies seem to be a better marker than anti-TPO antibodies [15,16]. It is also reported that scattered lymphocyte infiltration is more frequent in benign nodules than PTCs [17].…”
Section: Studies With Surgical Specimensmentioning
confidence: 91%
“…The presence of AITD on final histopathology was associated with thyroid carcinoma risk in our study. The previous data on this relationship was contradictory . However, two large meta‐analyses supported that a significant association was present between thyroid autoimmunity and occurrence of thyroid cancer .…”
Section: Discussionmentioning
confidence: 96%
“…The previous data on this relationship was contradictory. [39][40][41][42] However, two large meta-analyses supported that a significant association was present between thyroid autoimmunity and occurrence of thyroid cancer. 43,44 Our results were consistent with studies that suggested an association between PTC and AITD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation